A Classical Model of the Class Struggle: A Game-Theoretic Approach - Mehrling, Perry G. (Journal of Political Economy, 1986)
The class struggle is formalized as a differential game in a strictly supply-side model, an approach that synthesizes the models of Lancaster and Goodwin. Four different steady-state equilibria are derived, each corresponding to different assumptions about the degree to which each class is organized to promote its own interests. In particular, the Goodwin growth cycle is shown to emerge from a world characterized by unorganized capitalists and workers, in which individuals ignore the effects of their own actions on economywide variables. More relevant for discussion of modern capitalism are the hierarchical equilibria, especially the codetermination equilibrium in which the existence of a full-employment equilibrium turns out to be problematic. Finally, comparative-statics results suggest that the incentives for technological change differ widely among the four regimes.